Pengaruh Fitur Layanan Pembayaran dan Top-Up Terhadap Kepuasan Pengguna Dana di Kabupaten Bogor - Randikatsany, Muhammad Nadhif; Adrian, Ferdisar; Ramadhani, Achmad; Syaddad, Jundi; Marpaung, Muhammad Nabiel Syakir; Ramadhan, Noorman; Putra, Bimo Bintara; Zulkahfi, Muhamad (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2026)
This study aims to analyze the effect of payment and top-up service features on DANA user satisfaction in Bogor Regency. The research method used is a quantitative approach with a causal associative research type. Data collection was conducted through a questionnaire consisting of 100 active DANA users using purposive sampling techniques, then analyzed using multiple linear regression analysis with the help of SPSS 26. The results of the study show that: (1) Payment service features have a positive and significant effect on DANA user satisfaction; (2) Top-up has a positive and significant effect on DANA user satisfaction; (3) Payment service features and top-up simultaneously have a significant effect on DANA user satisfaction. This study concludes that the completeness of payment service features, the ease of the top-up process, the diversity of top-up methods, and the availability of promotional programs are key factors in increasing DANA user satisfaction. The practical implications of this study are the need to optimize payment service features, improve promotional programs and cashback on top-up services, and strengthen security systems to maintain and increase user satisfaction in the face of increasingly competitive digital wallet industry competition.